Multireader assessment as an alternative to reference assessment to improve the detection of radiographic progression in a large longitudinal cohort of rheumatoid arthritis (ESPOIR). Issue 1 (4th January 2017) - Gandjbakhch, Frederique; Granger, Benjamin; Freund, Romain; Foltz, Violaine; Jousse-Joulin, Sandrine; Devauchelle, Valerie; Afshar, Mona; Albert, Jean David; Bailly, Florian; Constant, Elodie; Biale, Lisa; Milin, Morgane; et al.
Abstract : Introduction: Structural damage progression is a major outcome in rheumatoid arthritis (RA). Its evaluation and follow-up in trials should involve radiographic scoring by 1 or 2 readers (reference assessment), which is challenging in large longitudinal cohorts with multiple assessments. Objectives: To compare the reproducibility of multireader and reference assessment to improve the feasibility of detecting radiographic progression in a large cohort of patients with early arthritis (ESPOIR). Methods: We used 3 sessions to train 12 rheumatologists in radiographic scoring by the van der Heijde-modified Sharp score (SHS). Multireader scoring was based on 10 trained-reader assessments, each reader scoring a random sample of 1/5 of all available radiographs (for double scoring for each X-ray set) for patients included in the ESPOIR cohort with complete radiographic data at M0 and M60. Reference scoring was performed by 2 experienced readers. Scoring was performed blindly to clinical data, with radiographs in chronological order. We compared multireader and reference assessments by intraclass correlation coefficients (ICCs) for SHS and significant radiographic progression (SRP). Results: The intrareader and inter-reader reproducibility for trained assessors increased during the training sessions (ICC 0.79 to 0.94 and 0.76 to 0.92), respectively. For the 524 patients included, agreement between multireader and reference assessment of SHS progression between M0 and M60 and SRP assessment were almost perfect, ICC (0.88 (95% CI 0.82 to 0.93)) and (0.99 (95% CI 0.99 to 0.99)), respectively. Conclusions: Multireader assessment of radiographic structural damage progression is comparable to reference assessment and could be used to improve the feasibility of radiographic scoring in large longitudinal cohort with numerous X-ray evaluations.